The Role of Principal Supervision in Improving Teacher Professionalism at SMAN 1 Batang Gansal Indragiri Hulu Regency Riau Province - Ahmad Ridwan; Yudistira; Hikmatun Zillah; Siti Khomisah (PT ARRUS Intelektual Indonesia, 2023)
Enhancing the professionality of educators is an essential component of guaranteeing the caliber of instruction in each and every educational establishment. The point of this research is to look at the professionalism of teachers at SMAN 1 Batang Gansal, to see how to improve the professionalism of teachers at SMAN 1 Batang Gansal, and to examine the contribution of principal supervision at SMAN 1 Batang Gansal, Indragiri Hulu Regency, Riau Province to teacher professionalism. The method that is being used is qualitative. Data is gathered from a variety of sources using techniques including classroom observations, document studies, and in-depth interviews. The research results reveal that in enhancing the professionalism of teachers at SMAN 1 Batang Gansal, various efforts can be made, such as pursuing higher education, attending training sessions, and organizing mentoring programs. Meanwhile, the principal of SMAN 1 Batang Gansal implements four supervision roles, namely coordinator, consultant, group leader, and evaluator. Additionally, the school principal also follows three stages in supervision: preparation, implementation, and reporting, as a systematic effort to enhance teachers' professionalism and consequently improve the quality of teaching.